ANALYSIS OF CONSUMER DECISIONS TO BUY PRODUCTS AT ALFAMART MEDAN RETAIL STORES USING PSYCHOLOGICAL FACTORS AS PREDICTORS - Nura Amalia Afan; Hidayati Purnama Lubis; Dennis Nathanael; Ellysa; Eka Soraya (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
This research uses four psychological factors as independent variable, consisting of motivation, perception, learning, and belief and attitude. This study uses a dependent variable, namely the purchase decision. This study aims to find the influence of psychological factors consisting of motivation, perception, learning, and beliefs and attitudes on purchasing decisions either partially or simultaneously. The research was conducted in Alfamart outlet located at Jalan Medan-Binjai Km. 12 Muliorejo Village Sunggal Sub-district Deli Serdang District - North Sumatra. Sampling of 97 respondents using the formula Zikmund. Samples were taken by purposive sampling. Data collection using questionnaires distributed to respondents who shop at Alfamart booth where the research is done, and the scale used is Likert scale. Data analysis using multiple linear regression in which data processing using SPSS 24 windows based auxiliary application. The tests include data quality testing consisting of validity test, reliability test, and classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, F test, t test, and test of determination. The results showed a positive and significant influence simultaneously motivation, perception, learning, and beliefs and attitudes on purchasing decisions. partially, only perception, learning which shows a positive and significant influence on purchase decision. The adjusted value of R Square obtained is 0.539 indicating that 53.9% of purchasing decisions can be obtained and explained by psychological factors consisting of motivation, perception, learning, and beliefs and attitudes, while the remaining 46.1% is explained by other factors or variables beyond the model such as advertising, brand image, discount, and others..